The analysis of organizational features of psychological help for cancer patients - Мухаровська, Інна Романівна (ScienceRise: Medical Science, 2016)
The ideas and internal setting of patients about psychological help mainly provide the parameters and specificity of organization and realization of medical-psychological help. Aim of research – to define the features of organization of medical-psychological help for cancer patients on the base of study of their needs and settings as to psychological influences. Contingent and methods of research. The interrogation of 245 cancer patients (134 women and 111 men) about the need for medical psychological help was realized on the base of Kyiv city clinical oncological center during 2012–2015 using the specially elaborated questionnaire. In the process of analysis of the received data patients were divided in 3 groups, depending on the stage of treating process: group 1 (G1, n=80) included patients at the diagnostic stage, group 2 (G2, n=86) – primary patients, 3 group (G3, n=99) – patients at the repeated visits as a result of relapse or continuation of disease. Results. In cancer patients at the different stages of treating process and with different stages of the course of pathology took place the psychological features that caused the differentiation of clinical tasks and forms of medical-psychological help. The important factor was the accessibility of psychological help: information for patients about the presence of specialist on psychic health, the schedule of psychological arrangements, the presence of psycho-educative materials directly in departments. Taking into account the fact that the people, who surround patient and closely communicate with him/her, also undergo the high distress level, there was the practical necessity for elaboration of medical-psychological arrangements for the relatives and friends of patients, for the medical staff. The involvement of patients into participation in psychological arrangements can be raised by the modeling of motivational factors. Conclusion. Medical-psychological activity in oncological medical institution must be the complex one, connected with the tasks of clinical practice, must help to renew the psychic health of patients, to form in them the adaptive attitude and effective strategy of behavior as to antitumor treatment